Psychological Impacts For Elementary Age Children In Learning PAI During The Covid-19 Pandemic - Susilo Surahman; Irmayanti Irmayanti; T. M. Haekal; Pandu Adi Cakranegara; Purniadi Putra (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study examines the analysis of the psychological impact of the COVID-19 pandemic on Islamic Religious Education (PAI) learning in elementary school-age children. This research uses descriptive research, namely research based on literature review which is described through descriptions using library sources such as books, journals, and laws and regulations related to the research topic. In this study, it was explained that the covid-19 pandemic had a major impact on the learning process that occurred in Indonesia because the learning carried out had to be online or online. Many obstacles faced by teachers and students in the learning process occur such as the difficulty of understanding the material to the increasing level of student stress that affects the mental and psychology of students. Therefore, efforts are needed to be made by teachers and parents to minimize the psychological impact that occurs. Efforts are being made to provide guidance, mentoring, and motivation given by parents to their children to improve students' learning mood so that learning motivation also increases. In addition, teachers as educators must improve skills in utilizing technology so that learning is carried out more interesting and fun